2003
DOI: 10.2134/agronj2003.1157
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Pressure on Beef and Grain Production of Dual‐Purpose Wheat in Argentina

Abstract: quality forage during the 3 to 4 mo of reduced forage production. Over the last two decades an increase in the The effects of three different grazing pressures on beef (Bos taurus) cropping area devoted to grain production has gradually and wheat (Triticum aestivum L.) grain production were studied at Pasman (Argentina) during a 3-yr study. Thirty hectares of the variety replaced pasturelands. Currently, owing to low profits 'Pincen' wheat were grazed with Angus heifers during 3 yr (1995)(1996)(1997) from grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 13 publications
4
22
0
4
Order By: Relevance
“…Despite the 25% grain yield penalty from forage removal in dual-purpose systems, economic analysis revealed considerably higher revenue in this system. The greater feasibility of dual-purpose systems compared with grain-only systems has been noted (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Arzadun et al (2006) evaluated the increase of beef weight versus the decrease of wheat grain yield at increasing grazing pressures in a dual-purpose system and concluded that increased grazing pressure (grazing height from 7 to 3 cm) was profitable for farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the 25% grain yield penalty from forage removal in dual-purpose systems, economic analysis revealed considerably higher revenue in this system. The greater feasibility of dual-purpose systems compared with grain-only systems has been noted (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Arzadun et al (2006) evaluated the increase of beef weight versus the decrease of wheat grain yield at increasing grazing pressures in a dual-purpose system and concluded that increased grazing pressure (grazing height from 7 to 3 cm) was profitable for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported on the economic advantages of dual-purpose systems compared with grain-only systems (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Th e dual-purpose system would be feasible if the forage value obtained is greater than any grain yield penalty from grazing/clipping.…”
Section: Crop Economics Production and Managementmentioning
confidence: 99%
“…Outros autores também observaram que a produtividade de grãos de trigo de duplo propósito é influenciada pela época de semeadura, pela intensidade de pastejo e pelo período de pastejo (Del Duca et al, 2000a;Arzadun, 2003;Berges, 2005).…”
Section: Resultsunclassified
“…Wheat is increasingly cultivated as a dual-purpose crop in several main wheat areas of the world, including the USA southern Great Plains [1,2], Australia [3,4], China [5] and the Argentinean Pampas region [6][7][8]. The reasons for this expansion are mainly the capacity of wheat to provide forage early in winter without excessively decreasing grain production.…”
Section: Introductionmentioning
confidence: 99%